Tinjauan Kriminologi Tindak Pidana Kekerasan Seksual Terhadap Perempuan Dan Anak : Studi Kasus Di Wilayah Kepolisian Resor Boalemo - Asrina Nggai; Dian Ekawaty Ismail; Avelia Rahmah Y. Mantali (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Acts of sexual violence against women and children are a threat that continues to occur anywhere in the world. Boalemo Regency is one of the districts that has experienced a fairly high increase in the number of cases of sexual violence against children. Based on information obtained by the author at the Boalemo Police, the number of cases Sexual violence in the last 3 years has increased by 55 cases. In 2020 there were 15 cases, in 2021 it increased to 18 cases and in 2022 cases of sexual violence increased to 22 cases and cases of sexual crimes against women, in 2019 there were 2 cases, in 2020 only 1 case, and in 2021 only 2 cases. This research aims to determine the factors that cause sexual violence against women and children and to determine the police's efforts to tackle acts of sexual violence against women and children. This research aims to find out what factors cause criminal acts of sexual violence against women and children in Boalemo Regency and what police efforts are in dealing with criminal acts of sexual violence against women and children in Boalemo Regency. The research method used is empirical legal research. The data obtained in this research is analyzed qualitatively, namely by collecting data and drawing conclusions to determine the results. The research results show that there are several factors that cause sexual violence against female children in Boalemo Regency, namely: alcohol, low education, unmet biological needs, the role of the victim, lack of religious education and pornography. And the police's efforts to tackle criminal acts of sexual violence against women and children in Boalemo Regency are: conducting outreach and providing information about sexual violence through social media.